No blinding trachoma in Guangxi, China - LiangHao; ZuoHui-Yi; DuYi; JiangLin-Zhi; TanShao-Jian (眼科学报; 卷 31, 编号 1 (March 2016): 《眼科学报》, 2016)
In 2005, Boost and Cho reported a high incidence of trachoma in rural areas of Guangxi, China (1). Ten years later, active trachoma has been controlled in this province in southern China.